A AN ANALYSIS OF THE USE OF EXTENSIVE READING IN TEACHING READING COMPREHENSION AT SMPN 1 PANGALE - Fajriani, Fajriani (English Language, Linguistics, and Culture International Journal, 2023)
This research aims to determine the implementation of extensive reading in teaching reading comprehension as well as to determine students’ perceptions of the use of extensive reading in teaching reading comprehension. In this study, the researcher used a qualitative case study design where the source of the research data was class IX of SMPN 1 Pangale, from the 25 students in class IX, the researcher took 5 students’ to be interviewed in the research sample using random sampling. The researcher collected data using observation and interview instruments. Observations were made to find out the formulation of the problem regarding the implementation of extensive reading in teaching reading comprehension. Whereas, the interview was conducted to determine the formulation of theproblem regarding students’ perceptions of the use of extensive reading in teaching reading comprehension. After achieving this research, the researcher concluded that the implementation of extensive reading in teaching reading comprehension has a good effect on the students’ reading comprehension. It could be seen from the steps or methods taken such as the teacher starting with greetings, praying, checking the attendance list, and conveying an outline of the scope of the material. Then the teacher gave a text according to the students’ abilities and desires such as narrative text. Next, asked students to read the text and then asked students to find out the extent of students reading comprehension. As it is known that many students were active when answering the questions of the English text. After that, the teaching-learning process ended by concluding and giving assignments to students. While the results of interviews of the students’ perceptions regarding the used of extensive reading in teaching reading comprehension have a good effect because most class IX students of SMPN 1 Pangale enjoy the learning-teaching process. This could be seen from the results of the interviews: First, most of the students agreed that extensive reading was effective to be applied in teaching reading comprehension. Second, increase students’ interest in reading and increase students’ knowledge of vocabulary. Third, extensive reading could increase students’ motivation to reading. Keywords: Analysis Extensive Reading, Reading Comprehension